Altered cell function and increased replication of rhinoviruses and EV-D68 in airway epithelia of asthma patients - Essaidi-Laziosi, Manel; Royston, Léna; Boda, Bernadett; Pérez-Rodriguez, Francisco Javier; Piuz, Isabelle; Hulo, Nicolas; Kaiser, Laurent; Clément, Sophie; Huang, Song; Constant, Samuel; Tapparel, Caroline (Frontiers in Microbiology, 2023)
Rhinovirus (RV) infections constitute one of the main triggers of asthma exacerbations and an important burden in pediatric yard. However, the mechanisms underlying this association remain poorly understood. In the present study, we compared infections of in vitro reconstituted airway epithelia originating from asthmatic versus healthy donors with representative strains of RV-A major group and minor groups, RV-C, RV-B and the respiratory enterovirus EV-D68. We found that viral replication was higher in tissues derived from asthmatic donors for all tested viruses. Viral receptor expression was comparable in non-infected tissues from both groups. After infection, ICAM1 and LDLR were upregulated, while CDHR3 was downregulated. Overall, these variations were related to viral replication levels. The presence of the CDHR3 asthma susceptibility allele (rs6967330) was not associated with increased RV-C replication. Regarding the tissue response, a significantly higher interferon (IFN) induction was demonstrated in infected tissues derived from asthmatic donors, which excludes a defect in IFN-response. Unbiased transcriptomic comparison of asthmatic versus control tissues revealed significant modifications, such as alterations of cilia structure and motility, in both infected and non-infected tissues. These observations were supported by a reduced mucociliary clearance and increased mucus secretion in non-infected tissues from asthmatic donors. Altogether, we demonstrated an increased permissiveness and susceptibility to RV and respiratory EV infections in HAE derived from asthmatic patients, which was associated with a global alteration in epithelial cell functions. These results unveil the mechanisms underlying the pathogenesis of asthma exacerbation and suggest interesting therapeutic targets.